Physical Characterization and In Vitro Evaluation of Dissolution Rate from Cefpodoxime Proxetil Loaded Self Solidifying Solid SNEDDS - Sharma, Pankaj K.; Shukla, Vikesh Kumar; Kumar, Anoop (Current Drug Delivery, 2022)
Background: Cefpodoxime Proxetil (CPD) is a broad-spectrum cephalosporin indicated in respiratory and urinary tract infections. CPD is a BCS class IV drug with pH-dependent solubility and has poor bioavailability. This study investigated the challenges of developing ternary components based on solid SNEDDS of CPD for in vitro dissolution rate enhancement and self-solidifying behaviour. Methods: Tween 80, Transcutol and PEG6000 were employed as surfactants, solvents and solidifiers for a base of ternary components to develop self-solidifying solid SNEDDS, respectively. Ternary phase diagrams were used to characterize solidifying behaviour of ternary components in different proportions. S-SNEDDS formulations were drawn on the solidification areas available in the phase diagram and characterized for IR, XRD, DSC and in vitro drug release in various pH media. Results: Ternary components for the preparation of self-solidifying solid SNEDDS were selected based on drug solubility. FTIR and DSC characterization studies ruled out any drug interaction between CPD and components chosen to prepare S-SNEDDS. CPD was transformed from a crystalline into an amorphous state in ternary dispersions as revealed from XRD data. Optimized formulation (S-S 1) demonstrated more than 95% of drug release irrespective of the pH environments of the medium. Calculation of dissolution efficiency and similarity factors indicate that S SNEDDS resulted in a higher drug dissolution rate over binary dispersion (p<0.01). The stability studies showed that the S SNEDDS were stable in performances and CPD assay. Conclusion: The present investigation provides an alternative approach for enhancing the CPD dissolution rate using self-solidifying solid SNEDDS exhibited solidification behaviour at ambient temperature conditions and drug loading, which could be exploited over conventional dosage form.
Keywords: Cefpodoxime proxetil